Relations between tangle and I concurrence for even n-qubit states. (November 2019) - Zha 查, Xin-Wei 新未; Miao 苗, Ning 宁; Li 李, Ke 轲
Abstract : Gilad Gour and Nolan R Wallach [ J. Math. Phys. 51 112201 (2010)] have proposed the 4-tangle and the square of the I concurrence. They also gave the relationship between the 4-tangle and the square of the I concurrence. In this paper, we give the expression of the square of the I concurrence and the n -tangle for six-qubit and eight-qubit by some local unitary transformation invariant. We prove that in six-qubit and eight-qubit states there exist strict monogamy laws for quantum correlations. We elucidate the relations between the square of the I concurrence and the n -tangle for six-qubit and eight-qubits. Especially, using this conclusion, we can show that 4-uniform states do not exist for eight-qubit states.